The State of Digital Freedom in Indonesia an Assessment of Online Censorship, Privacy, and Free Expression - Hera Alvina; Lis Julianti; Anak Agung Putu Wiwik Sugiantari; I Wayan Wahyu Wira Udytama (Journal of Digital Law and Policy, 2022)
This article provides an assessment of the state of digital freedom in Indonesia, with a focus on online censorship, privacy, and free expression. The research methodology used in this study was a combination of normative legal approach and literature review, which provided a comprehensive analysis of the legal framework that governs digital rights in Indonesia. The discussion highlights the importance of human rights in the digital realm, and how the legal framework in Indonesia aligns with international human rights standards. The study found that the current state of digital freedom in Indonesia is mixed, with laws and regulations in place to protect privacy and freedom of expression, but concerns about online censorship and restrictions on these rights in practice. The implementation of laws such as the ITE Law has led to the prosecution of individuals for online speech, raising concerns about the impact on freedom of expression. To improve the state of digital freedom in Indonesia, several suggestions are made. Firstly, the implementation of laws and regulations related to digital rights must be consistent with international human rights standards. Secondly, efforts should be made to address the gaps between the legal framework and the reality of digital rights on the ground. This may involve greater transparency and accountability in the enforcement of laws and regulations related to digital rights. Additionally, there is a need for greater public awareness and education about digital rights, both among citizens and among policymakers and law enforcement officials.